HEGEMONI KEKUASAAN DALAM LIRIK LAGU RAP “PANOPTIKANUBIS” KARYA HOMICIDE - Yakobus M. Langkelang Niron; Karolus Budiman Jama (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
Lyrics in the flow of rap songs have a major role as a producer of meaning and aesthetics of a rap song. The concept of rap song lyrics has similarities with poetry and prose so that it can be said to be a literary text type. This study aims to examine the meaning comprehensively and described the forms of hegemony of power expressed in the lyrics of the rap song entitled "Panopticanubis" by Homicide. This study used a qualitative method with a content analysis approach. The data that is the focus of this research are words and phrases and clauses. Gadamer's hermeneutical theory is used as the main analytical knife to dissect the text and Gramsci's perspective on hegemony theory is used as a supporting theory. The results of the study prove that there are language variants or stylistics to produced meaning, including figurative language, scientific terms, and loan words. This song is interpreted as a concern about the formation of ideology and the hegemony of power that appears in the lyric text. The ideological formations contained in the text include imperialism, authoritarianism, feudalism, capitalism, neoliberalism, socialism. The forms of hegemony of power stated in the text include the power of the political community covering economic, political, social, technological and information aspects as well as defense. Meanwhile, the hegemony of civil society only occurs in the social aspect.